Na przekór stereotypom - trudne dziedzictwo ziem pogranicza. Zarys problemu na przykładzie Warmii i Mazur: Kilka refleksji na przykładzie Warmii i Mazur = Contrary to stereotypes - the difficult heritage of the borderlands. A few reflections on the example of Warmia and Mazury - Lewandowska, Izabela (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents stereotypes concerning the history of Warmia and Mazury, i.e. the southern part of the former Prussian lands, which has been within the borders of the Polish state since World War II. The introduction discusses stereotype, borderlands and cultural heritage, in relation to the area of the current Warmian-Masurian Voivodeship.
Keywords: Warmia i Mazury; stereotypy; pogranicze; dziedzictwo kulturowe; stereotypes; borderland; cultural heritage